The Application of Transesophageal Echocardiography in Mitral Valve Repair With Tendon Reconstruction - Zhou, Li; Gu, Ji-wei; Wang, Yun; Ye, Jing-jing; Wang, Fang; Wang, Ting-ting; Jiang, Bo; Na, Li-sha (Frontiers in Surgery, 2020)
Objective: To investigate whether tendon reconstruction during mitral valve repair can be effectively guided by transesophageal echocardiography (TEE), using the mid-esophageal bi-commissure view, bicaval view and the aortic valve–mitral valve transition short-axis view. Methods: A total of 40 patients that underwent mitral valve repair with artificial tendineae were recruited. Before the operation, conventional transthoracic echocardiography was used to determine whether mitral valve repair would be possible. Following intraoperative anesthesia, two-dimensional and three-dimensional TEE reconstructions were used to assess the state of the valve and tendon and to make a repair plan. Results: TEE accurately diagnosed single functional tendon rupture and predicted single artificial tendon implantation in 88% of cases (23/26). TEE accurately diagnosed single functional tendon rupture and predicted the implantation of two artificial tendons in 100% of cases (4/4). TEE accurately diagnosed two or more functional tendon ruptures and predicted the implantation of two artificial tendons in 100% of cases (5/5). The length of the tendon cord predicted by TEE (2.45 ± 0.15 mm) was not significantly different (P > 0.05) from the length of the cord that was actually implanted (2.31 ± 0.11 mm). TEE also accurately predicted the size of the annuloplasty ring in 86% of cases (33/38), with differences of 2 mm or less compared to the size of the ring that was actually implanted. Conclusion: Both the mid-esophageal bi-commissure view, bicaval view and the short-axis view of the aortic valve–mitral valve transition can reduce the difficulty of tendon reconstruction by helping to determine what length of tendon and what size of artificial annulus are required.